Efektivitas Pelatihan Komunikasi Untuk Meningkatkan Keterampilan Komunikasi Siswa Kejuruan Jurusan Akomodasi Perhotelan - Ridha, Andi Ahmad (Universitas Medan Area, 2018)
This study aims to determine the effectiveness of effective communication training on communication skills of vocational students in hospitality accommodation. This research uses quantitative experimental method with one group pretest posttest design. The subjects consisted of 6 students of vocational schools majoring in hospitality accommodation with poor communication skills. Intervention given to the subject is in the form of effective communication training. The research instrument used is learning evaluation and rating scale observation sheet. Data analysis was done descriptively and using statistical analysis of wilcoxon test. The results showed that there was an increase in knowledge and communication skills possessed before and after students were given effective communication training. The findings of this research can be used as a reference in developing communication skills of vocational students in hospitality accommodation.Â